The Spiritual Implications of Wheat in the Ethiopian Orthodox Tewahedo Church: A Study of Scripture, Liturgy, and Tradition - Muhammad Ridwan; Belay Sitotaw Goshu (Britain International for Academic Research (BIAR-Publisher), 2025)
Abstract: The Ethiopian Orthodox Tewahedo Church (EOTC) possesses a rich theological tradition in which material elements serve as vehicles for spiritual truth. Among these, wheat occupies a distinctive place, appearing throughout Scripture, liturgy, and living tradition. Yet the full spiritual implications of wheat within this tradition have received limited scholarly attention. Purpose: This study investigates the spiritual implications of wheat in the EOTC, examining its significance across three interconnected dimensions: scriptural revelation, liturgical enactment, and living tradition. The research aims to articulate how wheat functions as a multivalent symbol of divine provision, ethical responsibility, and eschatological hope. Methods: The study employs a qualitative approach combining biblical exegesis of Ge'ez texts (including the broader Ethiopian canon) with liturgical theology and analysis of traditional practices. Primary sources include the Book of Enoch (1 Enoch), the Book of Jubilees, and documented liturgical practices, particularly the preparation and distribution of Nifro (boiled wheat) at funerals and memorial services. Findings: The investigation reveals that wheat in the EOTC functions as a threefold symbol. First, scripturally, it signifies God's covenantal provision (Deuteronomy 8:8) and becomes a test of righteousness through the warning against consuming the